A Framework for Determining Population-Level Vulnerability to Climate: Evidence for Growth Hysteresis in Chamaecyparis thyoides Along Its Contiguous Latitudinal Distribution - Pederson, Neil; Leland, Caroline; Bishop, Daniel A.; Pearl, Jessie K.; Anchukaitis, Kevin J.; Mandra, Tessa; Hopton-Ahmed, Myvonwynn; Martin-Benito, Dario (Frontiers in Forests and Global Change, 2020)
The impact of ecological and climatological factors on individual organisms over time and space is inherently complex and creates substantial uncertainty about how climate change will influence the global biosphere. To understand some of this complexity, we investigated the factors influencing individual growth of Chamaecyparis thyoides over 61 years within 18 populations across the ca 1500 km and 11 degrees of latitude. We then applied a vulnerability framework to understand how the variability of tree growth response to climate varies between populations and regions across our network. Surprisingly, we found the growth of trees in the central portion of our network responded more synchronously to warming and drought than trees in the southern end of our network, suggesting greater vulnerability in the central populations with continued warming. Our analyses and framework approach revealed substantial complexity in growth responses to climate within and between populations. We found potential resiliency within all populations, but higher inter-population than intra-population variability in response to climate. We found that latitude was an important proxy for the growth response to temperatures during the non-growing season and spring, but that ecosystem structure can modify the growth response and vulnerability to drought during the summer. The range of growth responses to warming is greater in the southern populations than in more northernly populations. This asymmetrical distribution of growth response across our study network provides evidence for a kind of ecological hysteresis, more southerly populations could be more resilient with warming. Despite the fact that this species primarily lives in wetlands, we found drought stress to be an important constraint on growth. Our study and analyses help to explain the disparities between forecasts of how climatic change might impact tree species and ecosystems over space.